Isolation and molecular characterization of leptospira interrogans and leptospira borgpetersenii isolates from the urban rat populations of Kuala Lumpur, Malaysia - Benacer, D.; Siti NurSheena, M.Z.; Fairuz, A.; Galloway, R.L.; Thong, Kwai Lin (NCBI, 2013)
Rats are considered the principal maintenance hosts of Leptospira. The objectives of this study were isolation and identification of Leptospira serovars circulating among urban rat populations in Kuala Lumpur. Three hundred urban rats (73% Rattus rattus and 27% R. norvegicus) from three different sites were trapped. Twenty cultures were positive for Leptospira using dark-field microscopy. R. rattus was the dominant carrier (70%). Polymerase chain reaction (PCR) confirmed that all isolates were pathogenic Leptospira species. Two Leptospira serogroups, Javanica and Bataviae, were identified using microscopic agglutination test (MAT). Pulsed-field gel electrophoresis (PFGE) identified two serovars in the urban rat populations: L. borgpetersenii serovar Javanica (85%) and L. interrogans serovar Bataviae (15%). We conclude that these two serovars are the major serovars circulating among the urban rat populations in Kuala Lumpur. Despite the low infection rate reported, the high pathogenicity of these serovars raises concern of public health risks caused by rodent transmission of leptospirosis.